2014
DOI: 10.1007/978-3-662-45803-7_25
|View full text |Cite
|
Sign up to set email alerts
|

Morphing Schnyder Drawings of Planar Triangulations

Abstract: Abstract. We consider the problem of morphing between two planar drawings of the same triangulated graph, maintaining straight-line planarity. A paper in SODA 2013 gave a morph that consists of O(n 2 ) steps where each step is a linear morph that moves each of the n vertices in a straight line at uniform speed [1]. However, their method imitates edge contractions so the grid size of the intermediate drawings is not bounded and the morphs are not good for visualization purposes. Using Schnyder embeddings, we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Techniques from our paper have been used in algorithms to morph Schnyder drawings [10], and algorithms to morph convex drawings while preserving convexity [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques from our paper have been used in algorithms to morph Schnyder drawings [10], and algorithms to morph convex drawings while preserving convexity [5].…”
Section: Resultsmentioning
confidence: 99%
“…We leave as an open problem to find a morph that uses a polynomial number of discrete morphing steps and uses only a logarithmic number of bits per coordinate. Barrera-Cruz et al [10] made a first step in this direction by solving the case where the two drawings are Schnyder drawings.…”
Section: Discussionmentioning
confidence: 99%
“…Our motivation in examining this question partly lies in the elegance of the mathematics, but it was also posed to us by Veronika Irvine (see [2,9]), who needed the characterisation to to create and classify "grounds" for bobbin lace drawings; this paper is a first step in this direction. Further, we note that our result relates to the problem of morphing from one planar graph drawing to another (see [1,8]). Previous work has characterised drawings that arise from the Schnyder algorithm (see [3]) in this context.…”
Section: Introductionmentioning
confidence: 83%
“…The only paper we are aware of where the resolution problem has been successfully addressed is the one by Barrera-Cruz et al [7], who showed how to construct a morph with polynomially-bounded resolution between two Schnyder drawings Γ 0 and Γ 1 of the same planar triangulation. The model they use in order to ensure a bound on the resolution requires that Γ 0 = ∆ 0 , ∆ 1 , .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we show how to construct morphs of tree drawings that simultaneously achieve a reduced number of morphing steps and a polynomially-bounded resolution. Adopting the setting of [7], we assume that Γ 0 and Γ 1 are grid drawings and we ensure that each morphing step produces a grid drawing.…”
Section: Introductionmentioning
confidence: 99%